1956
DOI: 10.1017/s0022029900008360
|View full text |Cite
|
Sign up to set email alerts
|

639. Some bacteriological aspects of commercially sterilized milk: I. Incidence and nature of spoilage

Abstract: Samples of sterilized milk from fifteen dairies in the Midlands have been examined, and seasonal variations were detected in the incidence of mesophilic and thermophilic sporeformer contamination. Seasonal variation in the rate of spoilage at 30° C. was also apparent.The lower incidence of contamination in summer was considered to be due to (a) less sporeformer contamination during milk production at the farm in the period when the cattle are not housed, and (b) increased processing times and temperatures in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1956
1956
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…'Summer' has been regarded as the 6 months from 1 May to 31 October. It has been shown by Nichols & Candy (6) and by Eidgway (9), that in winter there is a greater incidence of contamination in commercial sterilized milk and more rapid spoilage in samples stored under conditions favourable to bacterial growth. It is suggested that the more rapid spoilage in winter is due to contamination by higher numbers of sporeformers, of which a greater proportion are the B. subtilisjB.…”
Section: ) Seasonal Variationmentioning
confidence: 99%
“…'Summer' has been regarded as the 6 months from 1 May to 31 October. It has been shown by Nichols & Candy (6) and by Eidgway (9), that in winter there is a greater incidence of contamination in commercial sterilized milk and more rapid spoilage in samples stored under conditions favourable to bacterial growth. It is suggested that the more rapid spoilage in winter is due to contamination by higher numbers of sporeformers, of which a greater proportion are the B. subtilisjB.…”
Section: ) Seasonal Variationmentioning
confidence: 99%